PERBEDAAN KOMPETENSI PETUGAS POLIKLINIK DALAM PENGGUNAAN SISTEM INFORMASI MANAJEMEN RUMAH SAKIT (SIMRS) SEBELUM DAN SESUDAH PELATIHAN DI RUMAH SAKIT UMUM DAERAH KECAMATAN MANDAU TAHUN 2018 - Manurung, Lisda Katerina (LPPM Universitas Muhammadiyah Sumatera Barat, 2019)
SIMRS is a series of activities that cover all hospital services starting from data collection,data processing, presentation of information and analysis therefore the HospitalManagement Information System must be carried out by each hospital in the delivery ofservices, therefore the need for officer competence includes knowledge, skills , attitude andbehavior in the use of SIMRS. Mandau District Hospital in the implementation of serviceshas been using SIMRS but is still constrained in its implementation so that it slows downthe service process. The purpose of the study was to determine the differences in polyclinicofficer competency in the use of hospital management information systems (SIMRS) beforeand after training at the Regional General Hospital of Mandau District in 2018. This typeof research uses analytical quantitative methods with pre post test with controls, andinterventions from each variable by conducting SIMRS training. Data analysis was carriedout by univariate and categorical pairing with marginal homogeneity test. The results ofthe study were differences in knowledge (P = 0.000), skills (P = 0.002), attitudes (P =0.000), behavior (P = 0.000) and competence (P = 0.000) before and after training inMandau District Hospital. In this study, the researchers concluded that there weredifferences in the competence of polyclinic officers in the use of SIMRS includingknowledge, skills, attitudes and behavior after SIMRS training. It is suggested the need forthe development of material and technical training for SIMRS, and monitoring andevaluating the competency of officers in the use of SIMRS.Keyword: Knowledge, Skills, Attitudes, Behavior, Competence, SIMRS